2018
DOI: 10.20944/preprints201803.0152.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exergy Analyses of Onion Drying by Convection: Influence of Dryer Parameters on Its Performance

Abstract: This research work is concerned in the exergy analysis of the continuous-convection drying of onion. The influence of temperature and air flow rate was studied in terms of exergy parameters. The energy and exergy balances were carried out taking into account the onion drying chamber. Its behaviour was analysed based on exergy efficiency, exergy loss rate, exergetic improvement potential rate and sustainability index.The exergy loss rates increase with the temperature and air flow rate augmentation.Exergy loss … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Increasing the input air temperature and IR power indeed enhanced the enthalpy of the drying chamber. Increased EIP due to elevated temperature was also reported for rough rice (Beigi et al, 2017), onion (Castro et al, 2018), and okra (Agarry et al, 2021; Okunola et al, 2021).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Increasing the input air temperature and IR power indeed enhanced the enthalpy of the drying chamber. Increased EIP due to elevated temperature was also reported for rough rice (Beigi et al, 2017), onion (Castro et al, 2018), and okra (Agarry et al, 2021; Okunola et al, 2021).…”
Section: Resultsmentioning
confidence: 73%
“…Okunola et al (2021) similarly reported an increase in ESI at higher air temperature and load density for drying Okra. Castro et al (2018) dried onion with a convective dryer and concluded a decrement in ESI with increasing the temperature and decreasing air flow rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations